2014
DOI: 10.1111/isqu.12139
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Americanism, Authoritarian Politics, and Attitudes about Women's Representation: Evidence from a Survey Experiment in Jordan

Abstract: A pillar of American foreign policy in the Middle East since September 11, 2001, has been promoting democracy, with particular emphasis on support for women's representation. Given high levels of anti‐Americanism in the region, does foreign pressure for policy reform undermine this project? Evidence from a nationally representative survey experiment in Jordan shows that an American endorsement of women in politics has no average effect on popular support for women's representation. Instead, domestic patterns o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 46 publications
1
43
0
Order By: Relevance
“…If we are to fully understand the impacts of international pressure, we need to examine how individuals actually respond to critical information and what this means for their support for their government's actions. Studies of transnational persuasion have shown that people may not act in a Bayesian manner, but instead rely on their own partisan political identities to cue how they interpret foreign comments (Bush & Jamal, 2014;Dragojlovic, 2015;Hayes & Guardino, 2011). Marinov (n.d.), for example, shows that disparaging foreign comments about democracy in Turkey could downgrade people's beliefs about freedoms in the country-but only if those comments were supported by their partisan political elites.…”
Section: A Theory Of Citizens' Responses To International Pressurementioning
confidence: 99%
“…If we are to fully understand the impacts of international pressure, we need to examine how individuals actually respond to critical information and what this means for their support for their government's actions. Studies of transnational persuasion have shown that people may not act in a Bayesian manner, but instead rely on their own partisan political identities to cue how they interpret foreign comments (Bush & Jamal, 2014;Dragojlovic, 2015;Hayes & Guardino, 2011). Marinov (n.d.), for example, shows that disparaging foreign comments about democracy in Turkey could downgrade people's beliefs about freedoms in the country-but only if those comments were supported by their partisan political elites.…”
Section: A Theory Of Citizens' Responses To International Pressurementioning
confidence: 99%
“…When quotas are seen as an illegitimate form of representation in such a way that quota recipients are not seen as deserving their positions, they may discourage political engagement (Zetterberg, 2009). Some scholars have noted that quotas are more likely to be perceived as illegitimate if their adoption is seen as originating from an outside body rather than pressure from domestic groups (Dahlerup, 2006; but see Bush & Jamal, 2014). In addition, it is possible in the case of Lesotho (and India) that a quota's symbolically exclusionary, rather than powersharing, nature may cause citizens to become less engaged with the political process (Kittilson & Schwindt-Bayer, 2010;Norris, 2008).…”
Section: Theoretical Framework: Why Should Gender and Gender Quotas Mmentioning
confidence: 99%
“…If leadership credibility impacts international support for US policies, it is important to consider whether this is a distinct effect from anti-Americanism in general. Individuals who dislike or are skeptical of the US may oppose US policies as a result (Bush and Jamal, 2015). The US's image around the world has been damaged by decades of war and controversial policies, not necessarily the perceived credibility of the current administration.…”
Section: The Us President and Foreign Policymentioning
confidence: 99%